The Boston Naming Test as a predictor of post-surgical naming dysfunctions in temporal lobe epilepsy - Escorsi-Rosset,Sara (2011)
OBJECTIVES: Patients that undergo epilepsy surgery for temporal lobe epilepsy (TLE) in the dominant hemisphere are more susceptible to naming deficits. The aim of the present study was to perform an observational retrospective study comparing two groups of patients for naming performance, those with left and right temporal lobe resections regarding the performance in naming by Boston Naming Test (BNT). METHODS: A total of 120 right-handed patients (52 right temporal lobe and 68 left temporal lobe), aged between 18 and 59, with pharmacoresistant mesial TLE were retrospectively analyzed. All patients underwent pre and postoperative neuropsychological assessment. RESULTS AND CONCLUSIONS : The BNT was a good predictor for possible post-surgical language deficits in patients submitted to left temporal lobectomy.